IMPLEMENTATION OF NORMS AND STANDARDS OF SCHOOLS ACCORDING TO RIGHT TO EDUCATION ACT 2009 - Rao, Boddepalli Govinda (International Journal of Psychosocial Rehabilitation, 2018)
All other human rights cannot be realized without education, which is a fundamental human right. It is a fundamental right that enables a person to live with dignity. Education produces workers for various economic sectors. India is home to the greatest concentration of illiterate people worldwide, according to UNESCO data. India has the greatest rate of child labor worldwide, and the primary cause of this is the great majority of Indians do not have access to formal education. Education’s main purpose is to liberalize a youngster and give them power. All things considered, education is a special investment in both the now and the future. The National Policy on Education is based on this fundamental idea.In our nation, every child now has the fundamental right to an education, or right to RTE. The Indian government established free and compulsory education for children aged 6 to 14 as a fundamental right. The purpose of compulsory education is to "protect" children’s right to an education because, when this need is ignored due to neglect or ignorance, children are unable to exercise their right to an education on their own. Kids should be allowed to experience childhood to the fullest. How can the structure be proper if the base is improper? On April 1, 2010, children’s rights to free and compulsory education went into effect. For the people of India, today is historic because, as stipulated by Article 21(A) of the Indian Constitution, the right to education will now have the same legal standing as the right to life. In India, this Act will guarantee free education for almost 92 lakh students. Every kid has the right to a high-quality primary education under the RTE Act. The collaboration of multiple departments at various levels is the main focus of this act. It also provides a donation-free atmosphere and does away with parent and kid interviews. In order to help potential teachers reach some of their goals in an uncertain future, this research serves to clarify why education quality is increasingly important and why they should be aware of the fundamental rights to an education.